ABOUT LESGAFT UNIVERSITY CONTRIBUTION TO THE DEVELOPMENT AND IMPROVING OF SPORTS COMPLEX «READY FOR LABOR AND DEFENSE» (TRP) - Vladimir A. Tajmazov; Vladimir U. Ageeve'ts; Yury F. Kuramshin (Высшее образование в России)
This article discusses the creation and development of the TRP sports complex, views the basic differences between the old and the new complex put into operation in September 1, 2014, considers its goals, objectives and principles of implementation. Special attention is paid to the role of the collective staff of Lesgaft University to the development of scientific, methodological, organizational, and pedagogical issues related to the creation and implementation in practice of the country's sports movement TRP sports complex at all stages of its formation and development.